FoxO3a involved in neutrophil and T cell survival is overexpressed in rheumatoid blood and synovial tissue. Issue 4 (11th May 2009) - Turrel-Davin, Fanny; Tournadre, Anne; Pachot, Alexandre; Arnaud, Béatrice; Cazalis, Marie-Angélique; Mougin, Bruno; Miossec, Pierre
Abstract : Objective: FoxO3a is a transcriptional factor implicated in cell cycle regulation and apoptosis. Since rheumatoid arthritis (RA) is associated with apoptosis defects, the expression level, regulation and phosphorylation status of FoxO3a was investigated in blood and synovium from patients with RA. Methods: In microarray experiments, an overexpression of FoxO3a mRNA was observed in blood from patients with RA compared with healthy controls. FoxO3a mRNA expression was quantified in polymorphonuclear cells (PMNs) and peripheral blood mononuclear cells from patients with RA by qRT-PCR. Total FoxO3a and phosphorylated FoxO3a (pFoxO3a) protein expression was analysed in blood leucocytes from patients with RA versus controls and in synovium from patients with RA versus patients with osteoarthritis (OA) by immunostaining. Results: FoxO3a mRNA and protein expression levels were increased in blood from patients with RA compared with controls. FoxO3a overexpression was primarily observed in PMNs. In synovium from patients with RA, both total and inactive phosphorylated FoxO3a proteins were detected. FoxO3a was detected primarily in the sublining T lymphocytes of synovium from patients with RA compared with the lining layer tissue from patients with RA and OA, underlying a role for FoxO3a proteins in inflammation in RA. Conclusion: The overexpression of FoxO3a in blood from patients with RA, particularly in PMNs, suggests a potential role for this gene in the pathogenesis of RA through increased survival of blood PMNs. In synovium from patients with RA, FoxO3a mainly detected in inflammatory aggregates may also regulate the chronic survival of T lymphocytes.